Analisis Sistem Antrian di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Karawang - Gina Khoirunnisa; Nelly Martini (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to clarify the phenomenon of the use of service facilities and find the level of optimization of the queuing system and total costs. The queuing system is a process related to waiting for people to get services efficiently. The study was conducted at the birth certificate registration queue system using 2 (two) facilities at the Karawang Regency Population and Civil Registry Office using the multiple lane queue model (M / M / S). the population in this study were visitors who came to the birth certificate registration counter. The data collection time for one month is July 2019 at 10:00 - 11:00 WIB. Based on the results of research, simulations, and discussion it can be concluded that the actual condition queuing system in the Karawang Regency's Population and Civil Registration Service uses 2 (two) lane facility counters, the optimal queuing system at the Karawang Regency's Population and Civil Registration Service uses 3 (three) counter facilities following the M / M / S queuing model. the cost efficiency obtained is Rp. 75,531, - per hour or Rp. 13,897,667 per month with a percentage of 75%.